Analisis Perubahan Tata Guna Lahan Terhadap Koefisien Limpasan Kota Pekanbaru Berbasis Sistem Informasi Geografis (SIG) - Putra, Rizki Rianda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The change in land use due to population growth affects the physical and environmental condition of the land. The information about the physical and environmental condition is imperative for the development of urban areas. The change in environmental condition can be observed based on the change of the runoff coefficient in Pekanbaru. The runoff coefficient value of an area is determined by the type of land use. In this study, a land-use-map which is based on the geographic information system (GIS) was used. The observed land-use-map was from the year 2006, 2012, and 2014. According to the land use mapping result, the plantation area was expanded from 18131.68 hectares in 2006 to 37364.58 hectares in 2012. The same trend occurred for residential area which was expanded from 11032.87 hectares in 2006 to 13461.17 hectares in 2012. In 2014, the residential area was further expanded to 15443.10 hectares. Based on the analysis results, the runoff coefficient in Pekanbaru City was increased from 0.31 in 2006 to 0.35 in 2012, and 0.36 in 2014. The division of land use was done by the area development (AD). The results show that the greatest change in runoff coefficient value occurred at the AD 5 which was changed from 0.36 in 2006 to 0.41 in 2012 and 0.44 in 2014. However at AD 1 the runoff coefficient remained constant at 0.55.Key words: Changes in land use, GIS, runoff coefficient